Biopterin Status in Dogs with Myxomatous Mitral Valve Disease is Associated with Disease Severity and Cardiovascular Risk Factors. (September 2014) - Reimann, M.J.; Häggström, J.; Mortensen, A.; Lykkesfeldt, J.; Møller, J.E.; Falk, T.; Olsen, L.H.
<x xml:space="preserve">Abstract</x> Background Endothelial dysfunction (ED) has been suggested to be associated with myxomatous mitral valve disease (MMVD) in dogs. Tetrahydrobiopterin (BH4) is an important cofactor for production of the endothelium‐derived vasodilator nitric oxide (NO). Under conditions of oxidative stress, BH4 is oxidized to the biologically inactive form dihydrobiopterin (BH2). Thus, plasma concentrations of BH2 and BH4 may reflect ED and oxidative stress. Objective To determine plasma concentrations of BH2 and BH4 in dogs with different degrees of MMVD. Animals Eighty‐four privately owned dogs grouped according to ACVIM guidelines (37 healthy control dogs including 13 Beagles and 24 Cavalier King Charles Spaniels [CKCSs], 33 CKCSs with MMVD of differing severity including 18 CKCSs [group B1] and 15 CKCSs [group B2], and 14 dogs of different breeds with clinical signs of congestive heart failure [CHF] because of MMVD [group C]). Methods Dogs underwent clinical examination including echocardiography. Plasma concentrations of BH2 and BH4 were measured using high‐performance liquid chromatography with fluorescence detection. Results Higher plasma BH4 and BH2 concentrations were found with dogs in CHF compared with all other groups (control, B1 and B2; P ≤ .001). Females had higher concentrations of BH4 and BH4/BH2 (P ≤ .0003). BH4/BH2 was found to decrease with age (P < .0001). Cardiovascular risk factors in humans such as passive smoking (P ≤ .01) and increased body weight (P ≤ .009) were associated with lower BH4 concentrations. Conclusions and Clinical Importance Age, sex, body weight, passive smoking, and cardiac status are associated with plasma biopterin concentration in dogs. Additional studies should clarify the clinical implications of the findings.